The Influence of Financial Compensation, Non-Physical Work Environment and Soft Skills on Employee Performance Through Organizational Commitment as an Intervening Variable at Mercu Buana University, Jakarta - Dewi Apriani; Lijan Poltak Sinambela (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to analyze the Influence of Financial Compensation, Non-Physical Work Environment, and Soft Skills on Employee Performance through Organizational Commitment as an Intervening Variable at Mercu Buana University, Jakarta. Data analysis was conducted through several tests, including the outer model measurement test (validity and reliability test), structural model test (R square, Path Coefficient, F-Square, Q-Square, Multicollinearity Test (VIF), Multiple and Simple Linear Regression Analysis), and hypothesis testing. The population of this study consisted of all non-teaching staff (non-lecturer employees) at Mercu Buana University, both permanent and contract employees, totaling 381 people, with a sample size of 150. Hypothesis testing in this study used the T-test with the provision that if the T-statistic value is greater than 1.979 and the P-value is less than 0.05, then the independent variable has a significant effect on the dependent variable. The results showed that Financial Compensation and Soft Skills have a positive and significant effect on Organizational Commitment and Employee Performance. Non-Physical Work Environment has a positive but not significant effect on Organizational Commitment and has a non-significant negative effect on Employee Performance. Through Organizational Commitment, Financial Compensation and Soft Skills have a positive and significant effect on Employee Performance, while Non-Physical Work Environment has a positive but not significant effect on Employee Performance.